Faham al-Sa‘adah (Kebahagian) menurut Islam: Analisis Matan Akidah Terpilih: The Concept of al-Sa‘adah (Happiness) in Islam: An Analysis on Selected Theological Texts - Zahari, Mior Muhammad Syahir; Shafie, Ahmad Bazli (Jurnal Usuluddin, 2024)
Happiness (al-sa‘adah) is an important discourse in the intellectual tradition of Islam. The discourse on happiness may be found in the al-Quran, the prophetic Hadith SAW, the works by mutakallimun, the works by philosophers, and the works by metaphysicians. This article aims to identify the discourse and the concept of al-sa‘adah in the selected works of mutakallimun namely al-‘Aqidah al-Tahawiyyah by Ahmad al-Tahawi (d. 321 H), al-‘Aqa’id by ‘Umar al-Nasafi (d. 537 H), Jawharah al-Tawhid by Ibrahim al-Laqani (d. 1041 H), and al-Kharidah al-Bahiyyah by Ahmad al-Dardir (d. 1201 H). This study research approach is qualitative. The data were collected through document analysis on the selected theological works as stated above and their commentary, also through content analysis by emphasizing on the discourse of al-sa‘adah. The data then analyzed descriptively. The study shows that (i) the discourses of al-sa‘adah in the text are in tandem with the discourses of al-shaqawah, (ii) a person’s al-sa‘adah and al-shaqawah had been determined by Allah SWT since eternality (azali), (iii) the forms of al-sa‘adah and al-shaqawah, (iv) it is not compulsory for Allah SWT to grant al-sa‘adah or al-shaqawah to whoever He wants, and (v) the concept of al-sa‘adah discussed by the mutakallimun does not change.